2023
DOI: 10.1109/access.2023.3244886
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Intelligent Vehicles (IoIV): An Intelligent VANET Based Computing via Predictive Modeling

Abstract: With the significant research and advancements in technologies, arose new applications such as autonomous driving and augmented/virtual reality. These applications required massive computational resources for the execution of various tasks. Utilizing vehicles resources in a distributed manner and collectively with the help of volunteer computing for various computational tasks is an emerging research area. The appropriate and intelligent decision in selecting a volunteer vehicle is crucial in this opportunisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…To intelligently meet the processing needs of vehicle applications, Haris et al [18] have suggested a VANETs architecture based on Intelligent Volunteer Computing. We provide criteria for choosing volunteers whose cars can complete the computationally demanding assignment.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To intelligently meet the processing needs of vehicle applications, Haris et al [18] have suggested a VANETs architecture based on Intelligent Volunteer Computing. We provide criteria for choosing volunteers whose cars can complete the computationally demanding assignment.…”
Section: Related Workmentioning
confidence: 99%
“…Step4: Using Equations ( 19)-( 22), determine R's value. Apply the approach of detour foraging by solving Equation (18). Then, using Equation (31), determine the new rabbit position's adaption value and update it.…”
Section: Detailed Implementation Of Laromentioning
confidence: 99%
“…In [58], to tackle the problem of scarcity of computational resources, a selection criteria is proposed to select volunteers' vehicles capable of executing the computationally intensive task. For the volunteer vehicle identification, the authors used various machine learning based regression techniques including LR, SVR, KNN, DT, RF, GB, XGBoosting, AdaBoost, and ridge regression.…”
Section: Ai For Resource Allocation In Iov Networkmentioning
confidence: 99%